2018
DOI: 10.1103/physrevc.98.024904
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical scaling for energies available at the BNL Relativistic Heavy Ion Collider to those at the CERN Large Hadron Collider

Abstract: )/S ⊥ does not depend on centrality, at the LHC energies a deviation from a linear behavior is observed towards the most central collisions. The influence of the corona contribution on the observed trends is discussed. The slopes of the p T particle mass dependence and the β T parameter from BGBW fits scale well with √ ( dN dy )/S ⊥ . Similar systematic trends for pp at √ s = 7 TeV are in a good agreement with the ones corresponding to Pb-Pb collisions at √ s NN = 2.76 and 5.02 TeV, pointing to a system-size-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…In addition, in Fig. 7 we demonstrate the iHKM results for mean transverse momentum of pions, kaons, and protons for seven centrality classes at the two collision energies, √ s NN = 2.76 TeV and √ s NN = 5.02 TeV, compared with the ALICE Collaboration experimental points [7,12,14]. We see that in the main iHKM points agree with the data, in particular the model reproduces a certain (up to 8-10%) increase of mean p T values at 5.02 A TeV against 2.76 A TeV, although at 2.76 A TeV the model slightly overestimates pion p T and proton p T in central events, while kaon mean p T are slightly underestimated at 5.02 A TeV in peripheral events.…”
Section: Results For √ S Nn = 502 Tev and Discussionmentioning
confidence: 97%
“…In addition, in Fig. 7 we demonstrate the iHKM results for mean transverse momentum of pions, kaons, and protons for seven centrality classes at the two collision energies, √ s NN = 2.76 TeV and √ s NN = 5.02 TeV, compared with the ALICE Collaboration experimental points [7,12,14]. We see that in the main iHKM points agree with the data, in particular the model reproduces a certain (up to 8-10%) increase of mean p T values at 5.02 A TeV against 2.76 A TeV, although at 2.76 A TeV the model slightly overestimates pion p T and proton p T in central events, while kaon mean p T are slightly underestimated at 5.02 A TeV in peripheral events.…”
Section: Results For √ S Nn = 502 Tev and Discussionmentioning
confidence: 97%
“…In a related study in Ref. [64], the average transverse momentum hp T i dependence of identified light flavor charged hadrons on the quantity τ n ¼ ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ð dN dy Þ=S ⊥ q has been investigated. Local parton-hadron duality and dimensionality arguments foresee the depletion of the ratio between the mean transverse momentum and the square root of the hadron multiplicity per unit of rapidity and unit of the colliding hadrons transverse overlapping area towards central collisions.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous studies these predictions were disputed based on existing measured data. The expected behavior of p T / (dN/dy)/S ⊥ as a function of collision energy and centrality for a wide range of energies [5] and for different collision systems at the same collision energy was systematically investigated in Ref. [6].…”
Section: Pos(panic2021)197 Pos(panic2021)197mentioning
confidence: 99%
“…These studies confirmed that the relevant scale in the gluon saturation picture predicted by CGC is the square root of the ratio between the particle density over unit of rapidity and the overlapping area of the colliding systems ( (dN/dy)/S ⊥ ). The particle densities were estimated based on available experimentally measured data [5]. For heavy-ion collisions, S ⊥ was estimated based on a Glauber Monte Carlo (GMC) approach by averaging the overlapping area of the nuclei over many events, as described in Ref.…”
Section: Pos(panic2021)197 Pos(panic2021)197mentioning
confidence: 99%